PLASMA CELL LEUKAEMIA: A RARE YET AGGRESSIVE PLASMA CELL DYSCRASIA WITH A VERY POOR RESPONSE TO CONVENTIONAL THERAPY - Khan, Najeebullah; Raza, Syed Shahmeer; Khan, Uzma Ikhtiar; ., Irfanullah; Abdullah, Hafez Mohammad Ammar; Hassan, Masroor; Hijaz, Asfandiar Shah Rukh; Hussain, Amer Kamal; Nadeem, Muhammad Daniyal (Journal of Ayub Medical College Abbottabad, 2019)
Plasma cell leukaemia (PCL) is a very rare plasma cell dyscrasia with a significant number of monoclonal plasma cells in the peripheral blood. It is diagnosed by the presence of ‰¥ 2x109 /L plasma cells in the blood or by plasma cells making up ‰¥20% of the leukocyte count. It can arise from a leukemic transformation of multiple myeloma, or more commonly it can be primary. Regardless of its origin, it carries a very dire prognosis. It responds very poorly to the traditional chemotherapy regimens used for multiple myeloma. We present the case of a 50 years old female who presented to our hospital with a complicated UTI and severe generalized body aches. She was diagnosed as a case of plasma cell leukaemia and was treated with cyclophosphamide and dexamethasone, however she failed to go into remission. Her condition deteriorated and she ultimately passed away 1.5 months after diagnosis. The recommended treatment for PCL is aggressive combination chemotherapy followed by stem cell transplantation. However, there is no consensus regarding the treatment of plasma cell leukaemia, and treatment should be individualized based on the patient profile. Once diagnosed, the prognosis is poor. Keywords: Plasma Cell Leukaemia; Multiple Myeloma; Plasma Cell Dyscrasia; Bortezomib